(untitled) (Euro-Latin American Journal of Administrative Law, 2024)
This article seeks to determine what are the causes that lead to the denaturation of the contracts for the provision of services and become a true employment relationship in accordance with the jurisprudence of the Council of State between the years 2016 and 2022. For this, a mixed type research investigation was carried out, with an analytical and hermeneutic paradigm, through an inductive method. The main conclusion is that it is the actions of the public authorities in the framework of the contracts, for the provision of services, which end up distorting this contract and turning the contractual relationship into a employment relationship.